1990
DOI: 10.1121/1.400107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postlingual deafness on speech production: Implications for the role of auditory feedback

Abstract: This study investigated some effects of postlingual deafness on speech by exploring selected properties of consonants, vowels, and suprasegmentals in the speech of seven totally, postlingually deafened individuals. The observed speech properties included parameters that function as phonological contrasts in English, as well as parameters that constitute primarily phonetic distinctions. The results demonstrated that postlingual deafness affects the production of all classes of speech sounds, suggesting that aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
1
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(119 citation statements)
references
References 0 publications
5
111
1
2
Order By: Relevance
“…In both adult humans and some songbirds, auditory feedback has been thought to guide the acquisition of learned sounds but to play less of a role in maintaining them (Konishi, 1965;Borden, 1979). It has been suggested recently that the severity of the effects of sudden deafness on speech depends on the age at onset of deafness (Waldstein, 1990). The agedependent differences reported by this author resulted from comparing the effects of onset of deafness in children versus adults.…”
mentioning
confidence: 68%
“…In both adult humans and some songbirds, auditory feedback has been thought to guide the acquisition of learned sounds but to play less of a role in maintaining them (Konishi, 1965;Borden, 1979). It has been suggested recently that the severity of the effects of sudden deafness on speech depends on the age at onset of deafness (Waldstein, 1990). The agedependent differences reported by this author resulted from comparing the effects of onset of deafness in children versus adults.…”
mentioning
confidence: 68%
“…In our deafened birds, syllables only became poorly modulated and noisy over time; repetitions of the same elements or notes within syllables increased and decreased in fundamental frequency. Such deficits are commonly reported in human vocalizations when hearing is impaired and are thought to be indicative of vocal control loss (Waldstein, 1990;Cowie, 1992). Thus, it seems that auditory feedback is also used to maintain stable syllables by continually correcting and refining vocal output to match previous iterations of the same syllable or to match a "memory" of what that syllable should be.…”
Section: Characteristics Of Song Degradation: Implications For Differmentioning
confidence: 99%
“…As adults, we can, simply by listening, learn to pronounce new words, or pick up regional accents, sometimes unconsciously. Experimental work has also shown that delayed or otherwise altered auditory speech feedback affects speech articulation (Houde & Jordan, 1998;Yates, 1963), and it is well-known that late onset deafness results in articulatory decline (Waldstein, 1989). Finally, neuropsychological research has shown that damage to left hemisphere auditory regions leads to deficits in speech production (Damasio & Damasio, 1980).…”
Section: Introductionmentioning
confidence: 99%